Does planning how to cope with anticipated barriers facilitate health-related behaviour change? A systematic review - Kwasnicka, Dominika; Presseau, J.; White, M.; Sniehotta, F. (Routledge, 2013)
Health-related interventions often prompt participants to plan how to cope with anticipated barriers to behaviour change, a technique known as coping planning. The purpose of this study was to review the evidence of the efficacy of prompting individuals to form coping plans as a technique for promoting health-related behaviour change. Electronic databases (MEDLINE, Embase and PsycInfo) and unpublished literature were searched for randomised controlled trials that allocated participants to the study conditions with and without prompts to form coping plans. Evidence was assessed for quality and narratively synthesised. Full text papers of 65 articles were assessed for eligibility and 11 papers were included in the review. Coping planning interventions appear to be efficacious when participants are supported in the process of forming coping plans. Combining action plans with coping plans seems to be more efficacious than using action plans only. The overall efficacy of coping planning is variable. Future interventions should consider potential moderators of the efficacy of such plans.